Carbon dioxide (CO2) laser cut quality using different feed rate and constant power level - Mohd Yusrizal, Mohd Ali (2008)
In manufacturing industries, laser is uniquely versatile tool for processing a remarkable range of metals, alloys, ceramics, glasses, polymers and composites. Light can be produced in pulsed or continuous form with different wavelength and power level. Laser processing has greater advantages compared to the traditional methods of industrial fabrication. It can be a profitable replacement for an existing technique. This is differs to the traditional machine tools that are normally designed for a particular purpose. There are a large number of parameters that control the laser cutting process. Each parameter has its own function which can affect the processing operation. The most important parameters to be considered is the laser power level range because there is significant relationship between power level and feed rate. The different laser cut power level range will produce different type of results depends on the feed rate. So, in this project sample of acrylic were cut on a CO2 laser cutting system with the variation in feed rate value and constant power level. The effect of both factors on width of heat-affected zone (HAZ), and striation frequencies have been studied. Manual calculation was used to develop graph that describes the effect on both factors on laser cut quality. As a result, the increased in feed rate were led to the decrease of the width of the heat-affected zone. The striation frequencies were increased with the increased of feed rate. Its means that, feed rate has important has a major effect on both the width of HAZ and striation frequency. To obtain better result, environmental effects such as room temperature, air ventilation, air humidity and lightning condition should be considered.